2023
DOI: 10.1021/acs.jpcc.3c06560
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature and Ambient Processed All Inorganic CsPbBr3 Perovskite Solar Cells: Stability Enhancement with AZO as an Electron Transport Layer

Tapas Das,
Naba kumar Rana,
Parul Garg
et al.

Abstract: All inorganic CsPbBr3-based perovskite solar cells (PSCs) have drawn great attention from researchers because of their high chemical and thermal stability in an open environment. In this work, we successfully replaced the high-temperature deposited mesoporous caping (m-TiO2) electron transport layer (ETL) with a low-temperature deposited aluminum-doped zinc oxide (AZO) ETL and fabricated all inorganic CsPbBr3 PSCs using copper­(I) thiocyanate (CuSCN) as a hole transport layer (HTL). The fabricated AZO-based de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Since the first use of organic–inorganic halide perovskite materials in solar cells was reported by Miyasaka and colleagues in 2009, there has been a dramatic increase in the power conversion efficiency (PCE) from 3.8% to 26.1%, establishing these cells as a cornerstone in the next wave of photovoltaic innovations. However, extensive research has demonstrated that the presence of organic components in the perovskite layer can lead to humidity and thermal instability, especially with regards to temperature tolerance, , significantly impacting the utilization of perovskite solar cells in practical scenarios. Particularly, in the face of abrupt temperature fluctuations, the presence of organic materials may exacerbate the structural degradation of perovskite materials, thereby adversely affecting their photoelectric conversion efficiency and operational lifespan.…”
Section: Introductionmentioning
confidence: 99%
“…Since the first use of organic–inorganic halide perovskite materials in solar cells was reported by Miyasaka and colleagues in 2009, there has been a dramatic increase in the power conversion efficiency (PCE) from 3.8% to 26.1%, establishing these cells as a cornerstone in the next wave of photovoltaic innovations. However, extensive research has demonstrated that the presence of organic components in the perovskite layer can lead to humidity and thermal instability, especially with regards to temperature tolerance, , significantly impacting the utilization of perovskite solar cells in practical scenarios. Particularly, in the face of abrupt temperature fluctuations, the presence of organic materials may exacerbate the structural degradation of perovskite materials, thereby adversely affecting their photoelectric conversion efficiency and operational lifespan.…”
Section: Introductionmentioning
confidence: 99%